2020
DOI: 10.1111/jse.12694
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis clarifies the evolutionary origin of Coffea arabica

Abstract: Interspecific hybridization events have played a major role in plant speciation, yet, the evolutionary origin of hybrid species often remains enigmatic. Here, we inferred the evolutionary origin of the allotetraploid species Coffea arabica, which is widely cultivated for Arabica coffee production.We estimated genetic distances between C. arabica and all species that are known to be closely related to C. arabica using genotyping-by-sequencing (GBS) data. In addition, we reconstructed a time-calibrated multilabe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 87 publications
(165 reference statements)
4
16
0
1
Order By: Relevance
“…After correcting for multiple substitutions, we observed a sharp peak in 4DTv value at 0.012 synonymous transversions per site in C. arabica . This corresponded to the period between 1.08 and 0.54 million years ago, during which the hybridization of two progenitor species ( C. canephora and Coffea eugenioides ) led to the emergence of C. arabica [ 43 ]. Comparisons between the 12,198 pairs of paralogous genes residing within 418 duplicated colinear blocks within the M. speciosa genome revealed a noticeable peak at 0.139, suggesting that M. speciosa has undergone a recent whole-genome duplication ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…After correcting for multiple substitutions, we observed a sharp peak in 4DTv value at 0.012 synonymous transversions per site in C. arabica . This corresponded to the period between 1.08 and 0.54 million years ago, during which the hybridization of two progenitor species ( C. canephora and Coffea eugenioides ) led to the emergence of C. arabica [ 43 ]. Comparisons between the 12,198 pairs of paralogous genes residing within 418 duplicated colinear blocks within the M. speciosa genome revealed a noticeable peak at 0.139, suggesting that M. speciosa has undergone a recent whole-genome duplication ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, phylogenetic studies confirmed that CAN and C. eugenioides can be considered the ARA's progenitor species, each providing half of ARA's genome. It has been assumed that these species hybridized between 1.08 million and 543 thousand years ago and that the emergence of ARA could be related to the environmental changes in East Africa during glacial-interglacial cycles in the last 1 million years [3].…”
mentioning
confidence: 99%
“…The genus Coffea consists of more than 100 botanical species ( Davis et al, 2006 ), however, the most cultivated species are Coffea canephora and Coffea arabica . C. canephora is diploid (2 n = 2x = 22 chromosomes) ( Denoeud et al, 2014 ), while C. arabica is a allotetraploid (2 n = 4x = 44 chromosomes) ( Tran et al, 2018 ) originated from natural hybridization between C. canephora and C. eugenioides ( Lashermes et al, 1999 ; Bawin et al, 2020 ). Among the more than 50 coffee-producing countries, Brazil, Vietnam, Colombia, and Indonesia are major producers, with Brazil being the largest producer by volume.…”
Section: Introductionmentioning
confidence: 99%